A discussion of the ethical implications of random drug testing in the workplace. Issue 4 (July 2015) - Christie, Timothy
This article discusses the scientific and ethical implications of random drug testing in the workplace. Random drug testing, particularly in safety-sensitive sectors, is a common practice, yet it has received little critical analysis. My conclusion is that there are important ethical challenges with these programs. Employers must ensure that every aspect of their policies are rooted in scientific evidence, linked rationally to the goal of workplace safety, and are ethically justifiable.